2015
DOI: 10.4103/0972-6748.181711
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and alcohol use disorder among male outpatients in a primary care setting in rural Puducherry

Abstract: Context:Alcohol use contributes to considerable morbidity and mortality worldwide. Screening for alcohol use and alcohol use disorder (AUD) at the primary care level can help in reducing this burden. While several community studies have been conducted to estimate the AUD, there apparently are no studies on opportunistic screening in a primary care setting in India.Aims:The aim was to estimate the prevalence of alcohol use and AUD in a primary care setting.Settings and Design:A hospital-based cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…The striking differences in alcohol use (and hazardous alcohol use) may also explain some of the sex imbalances in TB cases in India and in our study population (where the PAF for alcohol in women was only 1.7%). [ 14 ] Alcohol treatment programs are few in this area and more may be needed;[ 15 ] by reducing alcohol use, TB cases would be fewer. [ 12 , 16 ] Furthermore, alcohol use results in poor TB treatment adherence and worse TB outcomes, including death;[ 17 , 18 ] closer integration between TB control programs and alcohol treatment programs may improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The striking differences in alcohol use (and hazardous alcohol use) may also explain some of the sex imbalances in TB cases in India and in our study population (where the PAF for alcohol in women was only 1.7%). [ 14 ] Alcohol treatment programs are few in this area and more may be needed;[ 15 ] by reducing alcohol use, TB cases would be fewer. [ 12 , 16 ] Furthermore, alcohol use results in poor TB treatment adherence and worse TB outcomes, including death;[ 17 , 18 ] closer integration between TB control programs and alcohol treatment programs may improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a greater prevalence of alcohol use (79.3% vs. 39.8%), alcohol use disorder defined as AUDIT >8 (60.9% vs. 10.9%), and a higher proportion of probable dependent users defined as AUDIT >20 (9.9% vs. 2.3%) among fishermen compared to general population of Puducherry. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…Few facility-based studies done in primary health-care (PHC) settings in India have found that the prevalence of alcohol use among male outpatient department (OPD) attendees were ranging from 38% to 63%. [ 9 10 11 12 ]…”
Section: Introductionmentioning
confidence: 99%